Cat Who Tailed a Thief - Braun, Lilian Jackson (New York : G.P. Putnam's Sons, 1997)
In the nineteenth installment in the popular mystery series, the village of Pickax experiences a rash of petty thefts and the murder of a flashy newcomer, sending Qwilleran off on his own investigation into the crime wave, with feline sleuths Koko and Yum Yum sniffing for leads
70314
Keywords: Qwilleran, Jim (Fictitious character) -- Fiction; Journalists -- Fiction. -- United States; Siamese cat -- Fiction. -- United States; Cats -- Fiction. -- United States; Detective and mystery stories